Virus reactivation in a non-cirrhotic HBV patient requiring liver transplantation after cessation of nucleoside analogue therapy. Issue 1 (January 2021) - Zhang, Han; Chen, Fang; Giang, Erick; Bao, Fei; Lauer, Georg M; Marsh, Christopher; Law, Mansun; Pockros, Paul J
Nucleos(t)ide analogues (NAs) are a mainstay of therapy for chronic hepatitis B (CHB) infections and have a profound effect on hepatitis B virus (HBV) suppression. We report a rare case of HBV reactivation in a CHB patient without cirrhosis following cessation of NA therapy that resulted in acute liver failure requiring liver transplantation. Investigation of the viral genetics and host immune responses suggest that viral mutations known to promote virus replication are associated with reactivation, whereas adaptive immunity to HBV remained defective in this patient. Viral sequencing may be useful for identifying mutations that are unfavorable for therapy withdrawal.